Book Review: Fei Victor Lim and Mercedes Querol-Julián (2024), Designing learning with digital technologies. Routledge. - Mariasophia Falcone (EuroAmerican Journal of Applied Linguistics and Languages)
Designing Learning with Digital Technologies, edited by Fei Victor Lim and Mercedes Querol-Julián (2024), is an insightful contribution to the ever-evolving conversation about how digital tools shape and influence teaching and learning practices. Grounded in multimodal and socio-semiotic theory, the volume centers the role of educators and teachers as empowered designers of learning. With a specific focus on post-pandemic teaching realities teaching realities, yet not limited by them, it offers empirical studies, theoretical insights, and practical tools to support innovative, inclusive, and sustainable digital pedagogy across a range of educational and cultural contexts.